ZERO TRUST ARCHITECTURE IN MODERN ORGANIZATIONS - Alisher Serikbayev (Modern American Journals, 2025)
With cyber threats becoming more complex and remote work becoming more common, traditional security models are becoming obsolete. This article examines the architecture of Zero Trust (ZTA), considering its key components: continuous verification, least privilege, and micro-segmentation . Based on current research up to 2025 and practical cases, the article examines the role of AI/ML and cloud solutions in strengthening ZTA. It concludes with recommendations for the phased implementation of this architecture in the enterprise environment.
Keywords: Zero Trust Architecture , cybersecurity , information security, AI/ML in security, Zero Trust Network Access (ZTNA), cloud security, digital transformation.